Technology of synthesis and electronic structure of triple barium–strontium–calcium carbonates for cathodes of microwave devices - V. I. Kapustin; I. P. Li; N. E. Kozhevnikova; E. F. Khudaigulova (Российский технологический журнал)
Objectives. Triple barium–strontium–calcium carbonates of various grades are widely used for depositing oxide coatings on cathodes of electrovacuum devices. Of all types of cathodes used in electrovacuum devices, oxide cathodes are among the most common, due to combining efficiency, durability, operation at relatively low temperatures, and a relatively low cost. The aims of this work were to: create a technology for the synthesis of triple barium–strontium–calcium carbonates with nonequilibrium phase compositions that comprise the triple carbonate proper and a pure barium carbonate phase; develop a quality control procedure for such a carbonate for using it as a component of the cathode material for microwave devices; study how the electronic structure of barium oxide crystallites is affected by doping microimpurities from other phases of the cathode material.Methods. The study used precision X-ray diffraction analysis and electron spectroscopy.Results. A technology was developed for the co-precipitation of triple barium–strontium–calcium carbonates from their nitrate salts. Under optimal precipitation conditions, this produces triple carbonate powders with nonequilibrium phase compositions. Electron spectroscopy showed that the parameters of the electronic structure of the crystallites are significantly affected by doping impurities of calcium, strontium, and nickel in barium oxide crystallites formed by heat treatment of triple carbonates.Conclusions. Calcium and strontium have a synergistic effect on the doping of barium oxide with the two other chemical elements. As well as efficiently controlling the quality of the nonequilibrium phase composition of triple carbonates, which is formed during the synthesis of triple carbonates by the titration method, precision X-ray diffraction analysis can be used to efficiently control the processes of agglomeration of nanoparticles or recrystallization of nanostructured phases formed during the synthesis of triple carbonates.